Uncontaining Mobility: Lessons from COVID-19: 2nd AMMODI (African Migration, Mobility and Displacement) Annual Keynote Lecture, 30 June 2022 (The Strategic Review for Southern Africa, 2022)
This keynote lecture argues that both the perpetrators of policed mobility and its victims can learn tremendous lessons from COVID-19’s nimble-footedness, which humbles racialised technologies of containment and politics of redlining or something akin to it. The talk asserts that using technological gadgets that are very good at making it possible for us to be present in absence and absent in presence, strangers at various borders could borrow a leaf from COVID-19 on how to compress time and space in ways that enable even unwanted wayfarers to see, hear, smell, feel and touch virtually, thereby regaining freedom of movement by crossing borders undetected. The world as a whole could learn from resilient philosophies of kinship and solidarity in Africa to approach mobility in a more humane manner. Priority would be less on containment and more on accommodation of the stranger and freedom of movement.
Keywords: Mobility; Africa; COVID-19; Incompleteness; Borders; Kinship and Solidarity